sosialisasi SOSIALISASI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA GURU SDN 49/III KOTO BARU SANGGARAN KECAMATAN DANAU KERINCI : SOSIALISASI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA GURU SDN 49/III KOTO BARU SANGGARAN KECAMATAN DANAU KERINCI - Rini Syevyilni Wisda; Yelni Erniyati (Jurnal Pengabdian Masyarakat, 2024)
This community service activity entitled "Socialization of the Implementation of the Independent Learning Curriculum among Teachers at SDN 49/III Koto Baru Sanggaran" aims to provide opportunities and space for teachers at SDN 49/III to be able to discuss, understand and design teaching materials in the components The independent curriculum in elementary schools is in accordance with rules or standards that are adapted to the needs and abilities of each school. This activity is also carried out to increase the capacity of senior (old) teachers and young teachers in designing fun learning in the classroom. The implementation of service activities was motivated by the large number of schools that had not implemented this curriculum in its entirety, this was because teachers were shocked, overwhelmed, did not understand the independent curriculum, as well as the lack of socialization and training for teachers. The method used was a participatory discussion approach in socialization activities. The result was the seriousness, enthusiasm and enthusiasm of the teachers in understanding through the discussion process. Apart from being enthusiastic, the teachers also have the courage to design, create and design learning programs, this can be seen when the teacher is willing to show the learning program that has been prepared.